Network Controls on Mean and Variance of Nitrate Loads from the Mississippi River to the Gulf of Mexico. Issue 6 (1st November 2019) - Crawford, John T.; Stets, Edward G.; Sprague, Lori A.
Abstract : Excessive nitrate loading to the Gulf of Mexico (GoM) has caused widespread hypoxia over many decades. Despite recent reductions in nitrate loads observed at local scales, decreases in nitrate loading from the Mississippi River basin (MRB) to the GoM have been small (1.58% during 2002–2012) with a low level of analytical confidence in this trend. This work seeks to determine the reasons why local‐scale improvements have not translated into reductions at the outlet of the Mississippi River. We estimated annual nitrate loads from 166 sites in the MRB over the 2002 to 2012 period to examine trends and variability. The Upper Mississippi and Ohio Rivers together dominate the average nitrate load to the GoM, but very large interannual variability is driven primarily by the Upper Mississippi River. Within the Upper Mississippi River basin, decreasing trends in nitrate loading were common and the greatest improvements occurred at sites with the highest initial nitrate loads (the worst water quality). However, these improvements were balanced with increasing nitrate loads in other parts of the basin, such that the mean trend in load was near zero. Although load reductions in either the Ohio or Upper Mississippi basins have the potential to reduce the loads to the GoM, the improvements have not yet been large enough or widespread enough to lead to a change at the outlet. This analysis provides a basin‐wide perspective on recent nitrate trends and the contribution of tributary basins to the mean and variability of nitrate loading to the GoM. Core Ideas: High nitrate loads to the Gulf of Mexico remained stable in the 2002 to 2012 period. Nitrate load trends in the Mississippi River Basin were mostly small and offsetting. Larger, more widespread decreases are needed to achieve larger reductions at the outlet. Variation in nitrate load is driven mostly by the Upper Mississippi River subbasin. Mean reductions in gulf hypoxic zone size could be disrupted by large interannual variation.